2017
DOI: 10.1186/s12909-016-0851-6
|View full text |Cite
|
Sign up to set email alerts
|

Learning global health: a pilot study of an online collaborative intercultural peer group activity involving medical students in Australia and Indonesia

Abstract: BackgroundThere is limited research to inform effective pedagogies for teaching global health to undergraduate medical students. Theoretically, using a combination of teaching pedagogies typically used in ‘international classrooms’ may prove to be an effective way of learning global health. This pilot study aimed to explore the experiences of medical students in Australia and Indonesia who participated in a reciprocal intercultural participatory peer e-learning activity (RIPPLE) in global health.MethodsSeventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 35 publications
(47 reference statements)
6
65
0
4
Order By: Relevance
“…Student centred pedagogies such as peer led learning activities are developing recognition as a fundamental aspect of many teaching programmes (Briggs and Doubleday, 2016;Reid and Duke, 2015). Many benefits to the student are demonstrated, including increased confidence in practising skills, better self-esteem, improved communication skills, developed critical thinking skills and an overall higher performance during studies (Ambrose, Murray, Handoyo, Briggs and Doubleday, 2016;Bates, 2016;Tunggal and Cooling, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Student centred pedagogies such as peer led learning activities are developing recognition as a fundamental aspect of many teaching programmes (Briggs and Doubleday, 2016;Reid and Duke, 2015). Many benefits to the student are demonstrated, including increased confidence in practising skills, better self-esteem, improved communication skills, developed critical thinking skills and an overall higher performance during studies (Ambrose, Murray, Handoyo, Briggs and Doubleday, 2016;Bates, 2016;Tunggal and Cooling, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Established in 2009, participants report improved attitudes to psychiatry, factual knowledge and cross-cultural understanding 28. Challenges to successful peer educational partnership include variable motivation and the need for sustained engagement with a structured curriculum 29. To address this, we piloted the use of a PBL structure and an mhGAP-IG curriculum in Aqoon.…”
Section: Introductionmentioning
confidence: 99%
“…Our study ndings are consistent with other published digitally-assisted global health learning models such as RIPPLE and Aqoon, which also found that students appreciated learning alongside their international peers. However these models were either pilot studies and, to our knowledge, have not been integrated into the curriculum for all students (21,22,27). GHCR has been integrated into our respective curricula since 2017.…”
Section: Discussionmentioning
confidence: 99%